On the impact of introducing advanced devices into a cognitive radio network - DOYLE, LINDA (IEEE, 2009)
Abstract?Cognitive Radio promises better spectrum utilisation through decentralised control, sensing and decision making. The devices are intended to be inexpensive, upgradeable and adaptable. However, introducing upgraded devices into a decentralised environment may cause unexpected results, the upgrades may require a critical mass to show any benefit, and may have an adverse impact on existing devices, which may deter their adoption. We study, in simulation, the gradual introduction of cognitive devices into an existing population using a spectrum access etiquette, in three different scenarios for the device capability. We show that the new devices gain immediate benefits, and that there is always an incentive to upgrade. We show that overall spectrum efficiency is improved. Finally, we show that there is no negative impact on existing devices, and that the introduction of cognitive devices may even improve the success rate of lesser devices.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering